Szczegółowa diagnoza logopedyczna dziecka z niepełnosprawnością intelektualną w stopniu umiarkowanym jako podstawa skutecznej terapii - Szurek, Mateusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Speech and language are important in the mental and emotional development of every human being. Various speech disorders that affect the daily functioning, communication and acquiring the basic human needs can disrupt the functioning of a person in society. In the case of people with intellectual disabilities, this is an oligophasia, or the speech disorder characteristic for people with reduced intellectual ability. In this article, the author draws attention to the importance of a detailed speech diagnosis, which is the basis for the later therapeutic process. He presents in on the example of a child with moderate-degree intellectual disability, using the Afa-Skala test, while at the same time demonstrating its usefulness in diagnosing the intellectually disabled children’s language disorders. In the final part of the text the author deals with the problem of speech therapy in children with these disorders.